Principles in power : Latin America and the politics of U.S. human rights diplomacy - Walker, Vanessa, 1978- (United States in the world., 2020)
"In the 1970s human rights advocates and U.S. government officials created a uniquely anti-interventionist, self-critical human rights agenda in Latin America and beyond. This book exposes the strained yet transformative relationship between these ambivalent allies"--